2022
DOI: 10.3389/fnut.2022.966500
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum cadmium and diabetes in the general population: A cross-sectional study from NHANES (1999–2020)

Abstract: BackgroundAssociations between serum cadmium and diabetes had been reported in previous studies, however there was still considerable controversy regarding associations. Studies in general population that investigated the effects of serum cadmium on diabetes were currently lacking. We designed this cross-sectional study among U.S. adults under high and low cadmium exposure to assess associations between serum cadmium and diabetes.MethodsThis cross-sectional study analyzed 52,593 adults who aged more than 20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In this study, nine cycles of NHANES data (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) were collected by the Centers for Disease Control and Prevention (CDC). NHANES is a multi-stage, strati ed, large, nationally representative study of the United States population that provides detailed information about the study design, interviews, demographics, etc [5,13,14] . Among the sample of 80,241 adults, who did not provide dietary information or other variables, were excluded (Fig.…”
Section: Study Population and Designmentioning
confidence: 99%
“…In this study, nine cycles of NHANES data (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) were collected by the Centers for Disease Control and Prevention (CDC). NHANES is a multi-stage, strati ed, large, nationally representative study of the United States population that provides detailed information about the study design, interviews, demographics, etc [5,13,14] . Among the sample of 80,241 adults, who did not provide dietary information or other variables, were excluded (Fig.…”
Section: Study Population and Designmentioning
confidence: 99%
“…Notably, a meta-analysis found that Cd exposure was positively associated with the risk of both type 2 diabetes and prediabetes with moderate-certainty evidence ( Filippini et al, 2022 ). However, a cross-section study from NHANES suggested Cd exposure upper the normal level was not associated with diabetes in the general people from 1999 to 2020 ( Gong et al, 2022 ). The reason for the inconsistency with our results may be the neglect of synergistic toxic effects from other metals and the prediabetes not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study showed that higher Mn intake was directly associated with a lower risk of type 2 diabetes in a population of postmenopausal women 7 . Previous study found a negative association between typical levels of serum Cd and diabetes risk in a United States of America population aged 20 years or older 8 . Kornhauser et al reported that plasma Se was negatively associated with the severity of diabetic nephropathy in patients with type 2 diabetes 9 .…”
Section: Introductionmentioning
confidence: 85%